2022
DOI: 10.1177/14680874221128353
|View full text |Cite
|
Sign up to set email alerts
|

Maximum reduction in greenhouse gas emissions by complete replacement of natural gas with pure hydrogen as a sole low reactive fuel in a RCCI engine

Abstract: In order to maximum reduction in hydrocarbon fuels consumption as the largest source of greenhouse gas emissions, the aim of this study is to evaluate a RCCI engine performance fueled with diesel fuel and pure hydrogen as sole low reactive fuel. For this purpose, a single-cylinder heavy-duty diesel engine with bathtub piston bowl profile and compression ratio of 14.88:1 is assessed that operates at its mid-load range from 9.4 to 13.5 bar gross IMEPs. In order to overcome the NOx challenge resulted from using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Industrially developed countries visualize achieving the so-called "hydrogen economy", a term coined in 1970 by U.S. scientists John Bockris and Lawrence Walter Jones based on the idea of partially or totally replacing hydrocarbons with hydrogen to significantly reduce greenhouse gases [36]. Technological and economic studies have demonstrated that although hydrogen is a secondary energy vector and is more costly than natural fuels, its use is economically feasible in today's world.…”
Section: Introductionmentioning
confidence: 99%
“…Industrially developed countries visualize achieving the so-called "hydrogen economy", a term coined in 1970 by U.S. scientists John Bockris and Lawrence Walter Jones based on the idea of partially or totally replacing hydrocarbons with hydrogen to significantly reduce greenhouse gases [36]. Technological and economic studies have demonstrated that although hydrogen is a secondary energy vector and is more costly than natural fuels, its use is economically feasible in today's world.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, due to the nature of low temperature combustion and the very lean burning of the air-fuel mixture, presence of significant levels of CO and HC emissions in the exhaust gases are the main disadvantages of applying RCCI combustion mode compared to CDC mode. 12 Meng et al 13 observed that both HC and thermal efficiency can be enhanced by reducing the intake air pressure. One of the critical parameters that determine the total reactivity of the combustion process is the mass ratio of low to high reactivity fuel.…”
Section: Introductionmentioning
confidence: 99%